2021
DOI: 10.3390/ijerph18031299
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Indoor Thoron Gas Concentrations Using a Radon-Thoron Discriminative Passive Type Monitor: Nationwide Survey in Japan

Abstract: As part of a nationwide survey of thoron (220Rn) in Japan, the indoor 220Rn gas concentrations in 940 dwellings were measured throughout one year, from 1993 to 1996, using a passive type 222Rn-220Rn discriminative monitor. The monitor was placed in a bedroom or a living room in each house for four successive three-month periods. The mean annual indoor 220Rn concentration was estimated from the four measurements in each house. The arithmetic mean, the median and the geometric mean for indoor 220Rn concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the second campaign organized from 1993 to 1996, a total of 900 measurements were collected. The average annual radon concentration was calculated as 16 Bq m −3 [94]. A third survey carried out from 2007 to 2010 covered 3500 dwellings.…”
Section: Japan (Ii)mentioning
confidence: 99%
“…In the second campaign organized from 1993 to 1996, a total of 900 measurements were collected. The average annual radon concentration was calculated as 16 Bq m −3 [94]. A third survey carried out from 2007 to 2010 covered 3500 dwellings.…”
Section: Japan (Ii)mentioning
confidence: 99%
“…Therefore, the counting rate resulting from the progeny accumulation effect in measurement cycle i, n p,i , was estimated using Equation (12).…”
Section: Algorithm For Correcting Progeny Accumulation Effect and Est...mentioning
confidence: 99%
“…Nevertheless, exposure to even a low level of thoron can result in a considerable effective dose in the respiratory tract due to the high-dose conversion factor of thoron progeny compared to that of radon progeny [1,6]. Additionally, numerous surveys have revealed that the indoor levels of thoron and its progeny are comparable to, or even higher than, those of radon and its progeny in many regions [7][8][9][10][11][12][13]. Therefore, the radiological risk associated with thoron warrants significant attention.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially altered Tn diffusion length due to dwelling characteristics (older type settings, building materials, exhalation rates, or wall surface status) and atmospheric or human-lifestyle-oriented ventilation rates in apartment and traditional styles might be the probable reasons for larger Tn variabilities. As the distribution of Tn gas typically depends on the distance from the room wall [44,45], we focused on the wall distances for RADUETs. The Tn concentration measured in the modern type was found to be lower (<20 Bqm −3 ) for different wall distant positions.…”
Section: Estimation Of Indoor Radon and Thoron Concentrations In Dwel...mentioning
confidence: 99%